2012
DOI: 10.1038/ismej.2012.128
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the distribution of segmented filamentous bacteria in humans, mice and chickens

Abstract: Segmented filamentous bacteria (SFB) are indigenous gut commensal bacteria. They are commonly detected in the gastrointestinal tracts of both vertebrates and invertebrates. Despite the significant role they have in the modulation of the development of host immune systems, little information exists regarding the presence of SFB in humans. The aim of this study was to investigate the distribution and diversity of SFB in humans and to determine their phylogenetic relationships with their hosts. Gut contents from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
132
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(139 citation statements)
references
References 31 publications
4
132
0
Order By: Relevance
“…A complex microbial community was insufficient for generating a robust population of Th17 cells in the gut of SPF mice lacking SFB (9, 10) and gnotobiotic mice colonized long term with human fecal contents (42). Although SFB has been detected in multiple vertebrate species (43), there exists only sparse evidence of a related microbe colonizing humans (43)(44)(45)(46). A recent study showed that a consortium of 20 symbionts from the feces of an IBD patient could induce Th17 cells in mice but failed to identify the active microbes in healthy people (11).…”
Section: Discussionmentioning
confidence: 99%
“…A complex microbial community was insufficient for generating a robust population of Th17 cells in the gut of SPF mice lacking SFB (9, 10) and gnotobiotic mice colonized long term with human fecal contents (42). Although SFB has been detected in multiple vertebrate species (43), there exists only sparse evidence of a related microbe colonizing humans (43)(44)(45)(46). A recent study showed that a consortium of 20 symbionts from the feces of an IBD patient could induce Th17 cells in mice but failed to identify the active microbes in healthy people (11).…”
Section: Discussionmentioning
confidence: 99%
“…SFB is highly sensitive to diet composition and, because of a large number of auxotrophies (75), SFB survives by establishing close proximity to the epithelial surface, and possibly symbiotic interactions with certain commensal bacteria (76). The few studies analyzing the potential symbiotic relationship between specific commensal bacteria and SFB indicate that members of the Bacteroides/Prevotella or Lactobacillus genus may be key to explain its maintenance and abundance in infants and mice, respectively (77,78). Moreover, a recent paper shows that decrease of SFB in the ileum corresponds to an increase of the Erysipelotrichi class (79).…”
Section: Discussionmentioning
confidence: 99%
“…SFB are gut commensal bacteria that colonize the ileum mucosa of various vertebrates, including humans, mice, rats, chickens, and pigs (5)(6)(7)(8). However, SFB colonization is host specific (9,10), and a direct interaction with the ileum mucosa may be required for regulating the differentiation of Th17 cells (2,4,10).…”
mentioning
confidence: 99%